2014
DOI: 10.1017/s1742058x14000125
|View full text |Cite
|
Sign up to set email alerts
|

When Organizations Matter

Abstract: Increasingly, scholars have argued that immigration politics are inseparable from racial politics, which implies that organizations and individuals who mobilize around racial group interests influence racial and immigration attitudes and behaviors. How does the racialpolitical context influence anti-immigration lawmaking? In what ways does this influence vary at different stages of lawmaking? To address these questions, we combine comprehensive datasets of racially conservative organizations and state immigran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 81 publications
(112 reference statements)
0
2
0
Order By: Relevance
“…Here, we see that reports of discrimination are lower in new destination counties (counties that experienced above average growth rates in the Mexican-origin population) that also experienced an exclusionary ordinance (see Figure 2). According to previous research, an increase in perceived threats among the dominant group appears to have more to do with change (growth rates) than the share of a racially minority population (Ebert et al, in press; Hopkins, 2010; Newman, Johnston, Strickland, & Citrin, 2012; Ramakrishnan & Wong, 2010; Walker & Leitner, 2011). As such, we would expect that if local political elites provide legitimacy for perceived threats to the dominant group in established destinations that activate discriminatory actions against Mexican Americans, then this process would also occur in counties experiencing rapid change in the population reporting Mexican ancestry.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Here, we see that reports of discrimination are lower in new destination counties (counties that experienced above average growth rates in the Mexican-origin population) that also experienced an exclusionary ordinance (see Figure 2). According to previous research, an increase in perceived threats among the dominant group appears to have more to do with change (growth rates) than the share of a racially minority population (Ebert et al, in press; Hopkins, 2010; Newman, Johnston, Strickland, & Citrin, 2012; Ramakrishnan & Wong, 2010; Walker & Leitner, 2011). As such, we would expect that if local political elites provide legitimacy for perceived threats to the dominant group in established destinations that activate discriminatory actions against Mexican Americans, then this process would also occur in counties experiencing rapid change in the population reporting Mexican ancestry.…”
Section: Resultsmentioning
confidence: 97%
“…Immigrants and their children seek the promise of upward mobility against the headwinds of economic uncertainty and discrimination from U.S.-born individuals and political elites (Bohon, Conley, & Brown, 2014; Silver, 2014). The enactment of exclusionary laws—laws that restrict the rights of and services accorded to immigrant groups—in states such as Alabama and Arizona has raised concerns that immigrant communities will face increased hardship as a result (Ebert, Estrada, & Lore, in press). Indeed, past research has found that restrictive climates and discriminatory experiences lead to inequalities in multiple arenas, such as political participation (De la Garza & Vaughan, 1984) and socioeconomic mobility (Silver, 2014; Turney & Kao, 2009).…”
mentioning
confidence: 99%